POTENSI PASAR RAKYAT DALAM MENINGKATKAN KESEJAHTERAAN PEDAGANG PASAR RAKYAT KECAMATAN TEBAS KABUPATEN SAMBAS DALAM PERSPEKTIF EKONOMI ISLAM - Mega; Kusnadi, iwan (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
This research is motivated by the traditional market which is increasingly left behind and there are indications that the market is one of the efforts in the process of increasing the welfare of traders in an economy. With this kind of business, it is hoped that it will enable traders to create better economic conditions than before. In order for this achievement to be carried out optimally, it is considered necessary to explore the existing potential to then be developed optimally. The data validity technique used is triangulation. Based and the results of the study it can be concluded that the potential of the people’s market in improving the welfare of the people’s market traders in Tebas distric in an Islamic economic perspective has the potential to be developed because it has the interest of buyers who are still classified as existing, the price offered is cheap and easily accessible by people from the lower class, products that are there are people’s markets that also have a variety of variations, a strategic market location, and close to he crowds, opposite the location of bus stops and the morning market, is also a potential. In terms of welfare, traders in people’s markets can be categorized as prosperous, that is, seen from the income earned,theybare able to provide sufficient to meet the necessities of life, as well as help the family economy. The fulfillment of welfare in the perspektive of Islamic economics has also been classified as fulfilled, it can be seen from the statements of traders who say that the results of this trade have been able to bring them to go on pilgrimage and umrah.